2003
DOI: 10.1089/152091503322250640
|View full text |Cite
|
Sign up to set email alerts
|

Design, Methods, and Evaluation Directions of a Multi-Access Service for the Management of Diabetes Mellitus Patients

Abstract: Recent advances in information and communication technology allow the design and testing of new models of diabetes management, which are able to provide assistance to patients regardless of their distance from the health care providers. The M2DM project, funded by the European Commission, has the specific aim to investigate the potential of novel telemedicine services in diabetes management. A multi-access system based on the integration of Web access, telephone access through interactive voice response system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 22 publications
0
65
0
2
Order By: Relevance
“…[10] A growing body of literature suggests that information technology (IT), such as computer, Internet and cell phone technology, holds great promise in enhancing diabetic care. [11][12][13][14] …”
Section: Introductionmentioning
confidence: 99%
“…[10] A growing body of literature suggests that information technology (IT), such as computer, Internet and cell phone technology, holds great promise in enhancing diabetic care. [11][12][13][14] …”
Section: Introductionmentioning
confidence: 99%
“…The difficulty of controlling blood glucose for subjects is evident in the lack of good control experienced by most people with type 1 diabetes: in a study of 25,833 people with type 1 diabetes by the T1D Exchange Clinic Registry, it was shown that the average glycosylated hemoglobin (A1C) was 8.3%, 3 above the recommended limit of 7% set by the American Diabetes Association. 4 In addition, 7% of those studied had experienced severe hypoglycemia with seizure or coma, and 8% had experienced diabetic ketoacidosis within the last year.…”
mentioning
confidence: 99%
“…27,28 This "global agent for diabetes care" would be based on wireless communication of first-tier devices (biological variables monitors, hormone infusers) with a smart assistant equipped with dual-mode low energy Bluetooth, 29 which communicates remotely with the diabetes center. Its structure would be defined as a three-layer approach (Figure 1…”
Section: Smart Telemedicine For Supporting Continuous Glucose Monitoringmentioning
confidence: 99%